International arbitration in Switzerland a handbook for practitioners - Geisinger, Elliott; Voser, Nathalie; Petti, Angelina M. (Kluwer Law International, 2013)
This book, since its first edition in 2004, has been widely used as a peerless practitioners' guide to international arbitration in Switzerland. Keeping in line with the first edition, this second edition describes in detail each phase of arbitral proceedings, from drafting the arbitration clause to challenge and enforcement of the award. The second edition continues to pay close attention to all aspects, including procedure before the arbitral tribunal, interim measures, confidentiality, the mediation alternative, and many other topics. The new edition has been extensively revised to take fully into account the newly amended Swiss Rules of International Arbitration, as well as numerous changes internationally, such as the revised ICC Rules and the revised UNCITRAL Rules.